Teacher Adequacy and Projected Needs: Challenges and Future Direction for Special Schools in Central Kalimantan - Piter Joko Nugroho; Theo Jhoni Hartanto; Holten Sion (STAI Hubbulwathan Duri, 2025)
Special education in Central Kalimantan Province faces significant challenges in ensuring quality education for children with disabilities, particularly regarding the availability and adequacy of competent teachers. The shortage of qualified educators negatively impacts learning outcomes and the overall effectiveness of state special schools (SLB). This study analyzes the adequacy and projected teacher needs in public SLBs over the next five years, while also exploring perspectives on teacher availability, workload, and learning quality. This research employs a mixed-methods approach with an explanatory sequential design, beginning with quantitative data collection and analysis, followed by qualitative exploration. The study involved 20 state SLBs in Central Kalimantan Province, utilizing descriptive statistics, teacher needs projection, and an interactive data model for analysis. Findings reveal serious gaps in the number and quality of teachers in state SLBs, hindering their capacity to deliver optimal education services for students with disabilities. The projected demand underscores an urgent need to address teacher shortages and improve instructional quality. The study highlights the importance of collaboration between the Central Kalimantan Provincial Government and local universities to accelerate the establishment of a special education (PLB) undergraduate program and enhance teacher training. Strategic action is crucial to improving special education services in Central Kalimantan. Strengthening teacher recruitment, training, and professional development will ensure that students with disabilities receive the support necessary for optimal growth and active participation in society.